Horrible Harry and the scarlet scissors - Kline, Suzy.; Wummer, Amy (New York : Viking, 2012)
"The kids in Room 3B are asked to draw posters of things that they love, and one of them will get to share his or her poster on TV"--
Keywords: Contests -- Fiction; Drawing -- Fiction; Schools -- Fiction; Behavior -- Fiction; JUVENILE FICTION / School & Education; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Art & Architecture